Evaluation of Some Material to inhibit Biofilm Formed by Acinetobacter baumannii Isolates - Noor Hussein Ahmad; Ghada A. Mohammad (Tikrit Journal of Pure Science, 2019)
The study has included the ability of Acinetobacter baumannii (isolated from clinical infections and hospital environment) to form a biofilm and investigated the possibility of inhibition this biofilm by using some materials: EDTA, five amino acids and five plant extracts.